Practicum mediated by photo-elicitation: Contribution to initial teacher training and the professional development of the teacher-tutor - Antonio Bautista-García-Vera; María Jesús Romera-Iruela; María Rosario Limón-Mendizábal; Belinda Uxach-Molina (Revista Española de Pedagogía, 2025)
This article investigates to what extent teaching degree students, during the three months of traineeship in schools, converse about, reflect on and rethink their tutors’ teaching practices through photo-elicitation processes to find professional development and improvement in both groups. A qualitative research methodology was used, focusing on the study of two cases. A photo-elicitation approach was implemented, guided by the trainee teachers to enable them to reflect on their tutors’ practice in the classroom and school, through photography. The results indicate that the educational situations captured by the student teachers are of an instructional and formative nature, with a predominance of denotative and connotative levels in the content of the first group and of denotative, connotative and affective levels in the second group. The photo-elicitation process followed led to the development of three main types of relationship between the trainee teachers and their tutors, defined as confirmation, contribution and reference, which fostered complicity, involvement, joint responsibility and mutual professional development.